Molecular identification of Azospirillum spp.: limitations of 16S rRNA and qualities of rpoD as genetic markers - Maroniche, Guillermo Andrés (2017)
Since their discovery, plant-growth promoting rhizobacteria from the genus Azospirillum have been sub-jected to intensive research due to their biotechnological potential as crop inoculants. Phylogeneticanalysis of Azospirillum spp. is carried out by 16S rRNA sequencing almost exclusively, but inconsis-tencies and low confidence often arise when working with close species. In this work, it was observedthat these difficulties might be explained by a high number of rRNA operons with considerable inter-genic variability within Azospirillum genomes. To search for alternative genetic markers from a list ofhousekeeping genes, the correlation between pairwise gene and whole-genome similarities was exam-ined. Due to its good performance, rpoD was selected for further analyses. Genus-specific primers for thePCR-amplification and sequencing of rpoD from Azospirillum spp. were designed and tested on 16 typestrains of different species. The sequences obtained were used for inferring a phylogenetic tree of thegenus, which was in turn used as a reference to successfully identify a collection of 31 azospirilla iso-lated from many different locations of Argentine. In addition, several strains that might represent novelspecies were detected. The results indicate that the sequencing of rpoD is a suitable alternative methodfor a confident molecular identification in Azospirillum spp.